Tracheoinnominate Artery Fistula Post Tracheostomy: A case report and literature review - O, Amy; Shanmugam, Ram Kumar Sharma; MohdYunus, Nik; D’Oliveiro, Jo-Lynn Jean; Yahaya, Zakinahbt; Hailani, Iskandar Bin (International Journal of Human and Health Sciences (IJHHS), 2019)
Tracheostomy is a common procedure in otorhinolaryngology and it is not without its own complications. Tracheoinnominate artery fistula is one of the late complication of tracheostomy. It commonly results in fatality if not detected and treated early. Herein, we present a rare case of a patient with underlying nasopharyngeal carcinoma post radiotherapy, cryotherapy and salvage neck dissection with tracheoinnominate artery fistula as a consequence of tracheostomy who defied statistics and was successfully stented. Objective of this case report is to create awareness regarding the differential diagnosis of massive bleeding from tracheostomy and immediate life saving measures the can be undertakenin addition to theneed to be vigilant in a patient with multiple risk factors that predisposes to the occurrence of tracheoinnominate artery fistula. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 238-240